Perception of Students Towards Active Learning in HEIs of Oman and Its Impact on Academic Performance (European Journal of Teaching and Education, 2023)
This study delves into the perception and impact of Active Learning (AL) practices among students in Omani Higher Education Institutions (HEIs). The study is conducted based on three primary objectives: 1. Assessing the prevalence of AL implementation in Omani HEIs. 2. Understanding students' perception of AL practices in Omani HEIs. 3. Evaluating the impact of AL on students' academic performance Employing a survey methodology, the study gathered data from 110 students enrolled in the Faculty of Business Studies at Arab Open University, Oman. Data analysis was conducted using SPSS Amos version software. The findings reveal that AL implementation in Omani HEIs is moderate. Students hold a favorable perception of AL, with 'Engagement of Students' emerging as the most positively perceived aspect. Notably, AL positively influences students' academic performance, with 'Engagement of Students' identified as the most significant predictor of performance. Interestingly, male students exhibited a stronger perception of AL and experienced greater performance benefits compared to their female counterparts. Considering these findings, the study recommends that HEIs in Oman actively promote the use of AL to enhance student engagement, motivation, and academic performance. Specifically, HEIs should prioritize developing and implementing AL strategies that foster active engagement among students.